Chronic kidney disease is associated with vascular smooth muscle dysfunction but not with endothelial dysfunction. (1st March 2018) - Iwamoto, Yumiko; Maruhashi, Tatsuya; Kajikawa, Masato; Oda, Nozomu; Kishimoto, Shinji; Matsui, Shogo; Hashimoto, Haruki; Aibara, Yoshiki; Yusoff, Farina Mohamad; Hidaka, Takayuki; Kihara, Yasuki; Chayama, Kazuaki; et al.
Abstract: Backgrounds: Nitroglycerine-induced vasodilation (NID) is usually assessed as a control test for flow-mediated vasodilation (FMD). However, NID per se is impaired in patients with high cardiovascular risk. The purpose of this study was to investigate the associations of chronic kidney disease (CKD) with NID and FMD. Methods: We measured NID and FMD in a total of 1567 adult subjects without end-stage renal disease (ESRD), 28% of whom had CKD as judged by measurements of estimated glomerular filtration rate (995 men and 572 women; mean age, 59.0 ± 16.9 years; age range, 18 to 92 years). Results: NID was significantly smaller in patients with CKD than in those without CKD (10.8 ± 6.0% vs. 12.7 ± 5.7%, P < 0.001). The prevalence of vascular smooth muscle dysfunction, defined as NID of less than the division point for the lowest quartile, was significantly higher in patients with CKD than in those without CKD (37.5% vs. 21.5%, P < 0.001). Multivariate analysis revealed that CKD was independently associated with vascular smooth muscle dysfunction (OR: 1.36, 95% CI: 1.02 to 1.81, P = 0.04). FMD was significantly smaller in patients with CKD than in those without CKD (3.1 ± 2.8% vs. 4.0 ± 3.0%, P < 0.001). The prevalence of endothelial dysfunction, defined as FMD of less than the division point for the lowest quartile, was significantly higher in patients with CKD than in those without CKD (31.7% vs. 23.1%, P = 0.002). However, CKD was not independently associated with endothelial dysfunction in an age- and sex-adjusted model (OR: 0.95, 95% CI: 0.71 to 1.26, P = 0.72). Conclusions: Non-ESRD CKD is independently associated with vascular smooth muscle dysfunction but not with endothelial dysfunction.